Large‐Diameter Carbon Nanotube Transparent Conductor Overcoming Performance–Yield Tradeoff. (23rd September 2021) - Zhang, Qiang; Nam, Jeong‐Seok; Han, Jiye; Datta, Sukanta; Wei, Nan; Ding, Er‐Xiong; Hussain, Aqeel; Ahmad, Saeed; Skakalova, Viera; Khan, Abu Taher; Liao, Yong‐Ping; Tavakkoli, Mohammad; et al.
Abstract: The floating catalyst chemical vapor deposition (FCCVD) method for producing single‐walled carbon nanotubes (SWNTs) has demonstrated great potential in transparent conductive film (TCF) application. In FCCVD, reducing the concentration of carbon nanotubes (CNTs) is a well‐agreed method of improving the conductivity of SWNT TCF, achieved by producing thinner and longer CNT bundles. However, this method decreases the yield dramatically, which has persisted throughout the TCF development. Here, the production of large‐diameter double‐walled CNT (DWNT) TCFs via FCCVD is reported, which overcomes the tradeoff between performance and yield. These TCFs of DWNTs with an average diameter of ≈4 nm have a low sheet resistance of 35 Ω sq −1 at 90% transmittance. The conductivity here aligns with the best‐performing SWNT TCFs reported to date, showing a production yield greater than two orders of magnitude. The main factor contributing to the high performance and yield is considered to be the large tube diameter, which greatly improves the yield threshold of CNT bundling and leads to long tube length and unique junctions broadening. Moreover, the application of DWNT TCFs in perovskite solar cells exhibits a power conversion efficiency of 17.4%, which has not been reported yet in indium‐free CNT‐based solar cells. Abstract : The transparent conductive film (TCF) of carbon nanotubes with large diameters of ≈4 nm and the applications in perovskite solar cells is reported. The TCF performance here aligns with the best‐performing TCFs of carbon nanotubes reported to date, showing a production yield greater than two orders of magnitude, which benefits from the large tube diameter.